Quality of Physical and Sensory of Super-native Chicken Breast Marinated with Herbs and Spices with Different Levels of Marination Concentration - Huda Oktafa; Agus Hadi Prayitno; Hatmiyarni Tri Handayani (Indonesian Center for Animal Research and Development (ICARD), 2023)
Super-native chickens result from crosses between male native chickens and laying hens. The diversification of processed products from super-native chicken can be developed into ready-to-cook products by marinating them with local herbs and spices. This research was conducted on the effect of marination concentrations of different local herbs and spices on the hedonic quality of super-native chicken breast. The research material consisted of super-native chicken breast, chili powder, sugar, salt, pepper, garlic, cinnamon, palm oil, lime juice, monosodium glutamate, and ginger. The treatment levels of marination concentration were 10, 20, and 30% of the weight of the meat. Physical quality parameters tested were color, pH value, moisture, cooking loss, water-holding capacity, yield, and hardness. Each treatment consisted of 3 replications. In addition, sensory quality was tested by a hedonic quality test by 40 untrained panelists. The hedonic quality parameters tested were color, flavor, taste, texture, tenderness, and juiciness. The data from the physical quality test were analyzed by analysis of variance. The hedonic quality test results were analyzed by non-parametric analysis through the Kruskal-Wallis hedonic test. If there was a significant difference (P0.05), the test was continued with Duncan's New Multiple Range Test. The results showed that the concentration level of different local herbs and spices marination could affect the physical quality (redness, pH value, and moisture) and sensory (color and texture) of super-native chicken breast. The marination concentration of local herbs and spices at 20% level was the best treatment based on hedonic quality with a smooth meat texture and a score of 3.98.